The Influence Of Price Perception, Product Quality, And Healthy Lifestyle On The Purchase Decision Of Sain Deli Healthy Food Products In Bandar Lampung - Amira Munira; Mahrinasari; Nuzul Inas Nabila (Cita konsultindo, 2026)
This research is motivated by the increasing public awareness of the importance of a healthy lifestyle, which drives changes in consumer behavior in choosing food, so that purchasing decisions are not only based on price but also on product quality and alignment with the healthy lifestyle being pursued. This study aims to determine the influence of price perception, product quality, and healthy lifestyle on the purchasing decision of Sain Deli healthy food products in Bandar Lampung. This study uses a quantitative approach with sampling techniques employing simple random sampling probability sampling. Data collection was conducted thru questionnaires distributed to 160 respondents who are consumers of Sain Deli in Bandar Lampung. The data obtained were then processed using SPSS version 27 software. The research results show that price perception, product quality, and a healthy lifestyle have a positive and significant impact on the purchasing decision of Sain Deli healthy food products. This study is expected to provide a deeper understanding of the factors influencing consumer purchasing decisions regarding healthy food products.